Functional abdominal pain, psychiatric illness, and life events. Issue 2 (February 1988) - Creed, F; Craig, T; Farmer, R
Abstract : Patients undergoing appendicectomy, attending a gastroenterology clinic or admitted to hospital after self-poisoning have been examined using the same reliable measures to establish whether life events and psychiatric illness preceded abdominal pain. Life events involving threat were experienced more commonly by those with organic and functional abdominal illness, compared with community comparison subjects. The greatest difference was with severe events, especially those involving the break-up of close relationships, which preceded the development of functional abdominal pain as often as they occurred before self-poisoning, and significantly more frequently than before the onset of organic gastrointestinal illness. Abdominal pain of recent onset, for which no organic cause is found, is often preceded by environmental stress, whether it presents to the surgeon or the physician. Those presenting in the clinic were older than those undergoing appendicectomy and had experienced more long lasting interpersonal difficulties. Many had psychiatric illness, but for the remainder the stress might either have caused colonic pain directly or led to consultation for abdominal pains that had not previously presented to a gastroenterologist.